Successful treatment of a refractory intestinal Behcet’s disease with an oncology history by Vedolizumab: a case report and literature review - Li, Ruixia; Li, Xiaofei; Zhou, He; Shi, Yanting; Wang, Fang; Wu, Tong; Liang, Jie (Frontiers in Immunology, 2023)
Objective: Behçet’s Disease (BD) is an intractable systemic vasculitis. When accompanied by intestinal symptoms, the prognosis is usually poor. 5-Aminosalicylic acid (5-ASA), corticosteroids, immunosuppressive drugs, and anti-tumor necrosis factor-α (anti-TNF-α) biologics are standard therapies to induce or maintain remission for intestinal BD. However, they might not be effective in refractory cases. Safety should also be considered when patients have an oncology history. Regarding the pathogenesis of intestinal BD and the specific targeting effect of vedolizumab (VDZ) on intestinal inflammation, previous case reports suggested that VDZ might be a potential treatment for refractory intestinal BD. Methods: We report a 50-year-old woman patient with intestinal BD who had oral and genital ulcers, joint pain, and intestinal involvement for about 20 years. The patient responds well to anti-TNF-α biologics but not to conventional drugs. However, biologics treatment was discontinued due to the occurrence of colon cancer. Results: VDZ was intravenously administered at a dose of 300 mg at 0, 2, and 6 weeks and then every eight weeks. At the 6-month follow-up, the patient reported significant improvement in abdominal pain and arthralgia. We observed complete healing of intestinal mucosal ulcers under endoscopy. However, her oral and vulvar ulcers remained unresolved, which disappeared after adding thalidomide. Conclusion: VDZ may be a safe and effective option for refractory intestinal BD patients who do not respond well to conventional treatments, especially those with an oncology history.